Bilateral bifid condyle mandibula features in panoramic radiography: a case report - Gunawan Gunawan; Ivony Fitria (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: The aim of this case report is to describe radiographically the specific features of bifid mandibular condyle that frequently found incidentally on panoramic radiographs. Case Report: A 24-year-old man came to the Installation of Dental Radiology RSGM UNPAD brought a referral letter for a panoramic photograph. From anamnesis is known patient have complaints of pain in the jaw joints left and right at the time of open mouth. Panoramic radiographs show mesioangular dental impaction of 48, and edentulous tooth 36 and presence of bifid condyle on the right and left condyle. Bifid condyle usually becomes incidental finding on routine panoramic radiographic examination. Bifid condyle features can be shown by depression or notch on the superior surface of condyle. Bifid condyle can provide a